KONTRIBUSI BUMDES TRIDADI MAKMUR TERHADAP PENINGKATAN KESEJAHTERAAN SOSIAL EKONOMI MASYARAKAT DESA TRIDADI KECAMATAN SLEMAN YOGYAKARTA - JUHARI SASMITO AJIE; ULUNG PRIBADI; ROSSI MAUNOFA WIDAYAT; GALIH DWI RIZQI J (GANEC SWARA, 2020)
National development is a concept, where the government will strive to achieve the welfare of society evenly and thoroughly. Through BUMDES (Village-Owned Enterprises) the national development plan can be realized if there is an active role of the village government and the community. This study aims to determine the governance and contribution of the existence of BUMDes Tridadi Makmur to improving the socio-economic welfare of the people of Tridadi Village, Sleman Jogyakarta District.This study uses a qualitative descriptive method, data collection using online media. The research result shows that 1). The management governance of BUMDes Tridadi Makmur, seen from the BUMDes organizational structure, has met the basic needs of the organization, with reference to the duties and functions and authorities that are adjusted to the conditions of the BUMDes development, 2). The existence of BUMDes has a social contribution, namely Tridadi Village has turned into a village as a tourist destination such as the Puri Mataram tourist vehicle and has been awarded an award by the Ministry of Village, Development of Disadvantaged Areas and Transmigration at the "2019 Archipelago Tourism Village with Advanced Category" event. Besides that, it has also contributed to absorbing the workforce, amounting to 135 people with the majority of Tridari Village residents and economically contributing to improving the welfare of the community